The Future of Bacterial Cellulose and Other Microbial Polysaccharides - Trovatti, Eliane [UNESP] (Tech Science Press, 2013)
Biobased polymers have been gaining the attention of society and industry because of concerns about the depletion of fossil fuels and growing environmental problems. Cellulose fibers are one of the most promising biopolymers to be explored as a component of composite materials with emergent properties for new applications. Bacterial Cellulose (BC), a special kind of cellulose produced by microorganisms, is endowed with unique properties. In this context, this perspective offers an overview about the properties of BC that would enable it to become a commodity. This includes an appraisal of the current BC market, as compared with other available biopolymers. The steps of the biosynthesis and purification of BC are also outlined, together with the difficulties that may be responsible for its future development, including the needs for making its production process(es) more attractive to industry. Other microbial polysaccharides are also discussed.
Keywords: Bacterial Cellulose; market; biopolymers; other microbial polysaccharides